Implementasi Sistem Manajemen Transportasi Cerdas melalui Aplikasi Trans Jatim-Ajaib 2.0 - Bernanda Anggita Davina Azzara; Agus Prastyawan (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
An intelligent transportation management system integrates information technology, electronics, and telecommunications to improve the effectiveness and efficiency of road transportation services. The East Java Transportation Agency implemented the Trans Jatim-Ajaib 2.0 application to enhance Trans Jatim Bus services in accordance with the Indonesian Minister of Transportation Regulation No. PM 76 of 2021. This study aims to analyze the implementation of the Trans Jatim-Ajaib 2.0 application and identify the supporting and inhibiting factors affecting its implementation. A qualitative descriptive approach was employed using Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure, complemented by Gerston’s framework for supporting and inhibiting factors. The findings indicate that internal communication among implementers has been effective; however, public information regarding application usage, route changes, and schedules has not been optimally delivered or integrated in real time. Human resources and supporting facilities are generally adequate, although limitations remain in customer service personnel, network connectivity, and data synchronization. Implementers demonstrate commitment to policy implementation, but complaint handling is relatively slow and incentives are unevenly distributed. Standard operating procedures and task allocation are well established, yet real-time service implementation is constrained by the high number of complaints and limited user information. Strengthening the information system and optimizing public services are therefore essential to improve the effectiveness of the application.